Properties of Biocomposite Fibers from Cellulose Nanowhiskers and Cellulose Matrix (Journal of Fiber Bioengineering and Informatics, 2012)
A series of self-reinforced, biocomposite fibers were successfully fabricated using Cellulose Nanowhiskers(CNWs) and cellulose matrix isolated from mulberry branch bark by wet spinning. The obtained CNWshave a diameter of about 20 nm and a length of 300-400 nm. The hybrid solutions containing less than9 wt% CNWs were miscible according to the rheological curves. Specially, the synergistic interactionsbetween fillers and matrix play a key role in reinforcing the composite fibers. The tensile strength andYoung's modulus of composite fibers at 65% relative humidity increased from 172 to 571 MPa and 2.06to 4.15 GPa with increasing CNWs content from 0 to 9 wt%.
Keywords: Cellulose; Cellulose Nanowhiskers; Self-reinforced; Biocomposite Fibers; Interfacial Interaction